DINAMIKA PERAN ISTRI DALAM PEMANFAATAN ERA DIGITAL DALAM UPAYA PENINGKATAN EKONOMI (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This  study examines the dynamics of wives’ roles in utilizing digital technology as a strategy to enhance household economic conditions. Digital transformation provides new opportunities for women, particularly wives, to engage in economic activities without abandoning their domestic responsibilities. Through digital platforms such as online marketplaces, social media, digital payment systems, and productivity applications, wives can operate home-based businesses, expand market reach, and increase family income. This research employs a qualitative approach using a literature review of scholarly journals and official reports related to the digital economy and women’s empowerment. The findings indicate that digitalization broadens women’s economic participation, strengthens financial independence, and enhances their contribution to household welfare. However, challenges such as low digital literacy, limited access to devices, and the dual burden of domestic work persist. The study highlights the need for digital training and family support to optimize wives’ participation in the digital economy.